CULTURE-THROUGH-LANGUAGE STUDIES IN SOCIO-PEDAGOGICAL WORK IN FRANCE - Liliia Shkoliar; Yevheniia Dehtiarova; Inesa Yermolenko (Novìtnâ Osvìta, 2018)
The article highlights the aim, the fundamental principles (democracy, openness, humanism, tolerance) and the main directions (culture-through language studies, social and legal support and protection, educational socio-pedagogical and psychological assistance, organisation of socially significant activities in an open environment) of socio-pedagogical work in France. The authors focus on culture-through language studies, its historical development and connection with the active migration policy of the country, characterises institutions which conduct culture-through language studies in socio-pedagogical work, namely: institutions of social and pedagogical infrastructure, local self-government bodies and local executive authorities. The article substantiates the necessity to focus the attention of specialists in socio-pedagogical work on the issues of the French language, history and culture in order to ensure that both the indigenous population and the representatives of other cultures living on the territory of the country are aware of their belonging to the French civil society. The authors highlight the importance of specially developed programmes and scientific and methodological resources for studying the linguistic, cultural and historical environment of the Republic which facilitate the process of francisation of the modern multicultural society of France.